FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN ANTENATAL CARE (K4) - Yuliana, Yuliana; Tunggal, Tri; Kristiana, Efi; Isnaniah, Isnaniah (Institut Teknologi dan Kesehatan Muhammadiyah Kalimantan Barat, 2026)
Background: The government has developed strategies and policies in the form of health improvement programs to reduce maternal mortality, including improving antenatal care (ANC) services. Data from the Amuntai Selatan Community Health Center (UPT Puskesmas) in 2024 showed that ANC coverage for K4 reached 77.43%, still below the Strategic Plan target of 86%. Health service utilization is influenced by several factors, such as knowledge, family support, and parity. Objective: To find out the factors related to ANC visits (K4) in the work area of the South Amuntai Health Center. Method: This study was designed as a cross-sectional analytical observational study. The sampling technique used total sampling with a sample size of 32 participants. Data were analyzed using the Chi-Square test. Result: A total of 11 pregnant women (34.4%) had incomplete ANC (K4) visits. A total of 9 pregnant women (28.1%) had insufficient maternal knowledge. A total of 9 pregnant women (28.1%) did not receive family support. A total of 13 pregnant women (40.6%) had high-risk maternal parity. There was a correlations between maternal knowledge (P-value 0.032), family support (P-value 0.016), and maternal parity (P-value 0.007) with ANC (K4) visits in the working area of the Amuntai Selatan Community Health Center. Pregnant women are expected to pay more attention to their pregnancies by attending ANC visits regularly and completely to detect and prevent pregnancy complications.